Machine model based Speed Estimation Schemes for Speed Encoderless Induction Motor Drives: A Survey - Mohan Krishna.S; Febin Daya.J.L (Bulletin of Electrical Engineering and Informatics, 2015)
Speed Estimation without speed sensors is a complex phenomenon and is overly dependent on the machine parameters. It is all the more significant during low speed or near zero speed operation. There are several approaches to speed estimation of an induction motor. Eventually, they can be classified into two types, namely, estimation based on the machine model and estimation based on magnetic saliency and air gap space harmonics. This paper, through a brief literature survey, attempts to give an overview of the fundamentals and the current trends in various machine model based speed estimation techniques which have occupied and continue to occupy a great amount of research space.